NLRC5 Deficiency Deregulates Hepatic Inflammatory Response but Does Not Aggravate Carbon Tetrachloride-Induced Liver Fibrosis - Quenum, Akouavi Julite I.; Shukla, Akhil; Rexhepi, Fjolla; Cloutier, Maryse; Ghosh, Amit; Kufer, Thomas A.; Ramanathan, Sheela; Ilangumaran, Subburaj (Frontiers in Immunology, 2021)
The nucleotide-binding leucine-rich repeat-containing receptor (NLR) family protein-5 (NLRC5) controls NF-κB activation and production of inflammatory cytokines in certain cell types. NLRC5 is considered a potential regulator of hepatic fibrogenic response due to its ability to inhibit hepatic stellate activation in vitro. To test whether NLRC5 is critical to control liver fibrosis, we treated wildtype and NLRC5-deficient mice with carbon tetrachloride (CCl4) and assessed pathological changes in the liver. Serum alanine transaminase levels and histopathology examination of liver sections revealed that NLRC5 deficiency did not exacerbate CCl4-induced liver damage or inflammatory cell infiltration. Sirius red staining of collagen fibers and hydroxyproline content showed comparable levels of liver fibrosis in CCl4-treated NLRC5-deficient and control mice. Myofibroblast differentiation and induction of collagen genes were similarly increased in both groups. Strikingly, the fibrotic livers of NLRC5-deficient mice showed reduced expression of matrix metalloproteinase-3 (Mmp3) and tissue inhibitor of MMPs-1 (Timp1) but not Mmp2 or Timp2. Fibrotic livers of NLRC5-deficient mice had increased expression of TNF but similar induction of TGFβ compared to wildtype mice. CCl4-treated control and NLRC5-deficient mice displayed similar upregulation of Cx3cr1, a monocyte chemoattractant receptor gene, and the Cd68 macrophage marker. However, the fibrotic livers of NLRC5-deficient mice showed increased expression of F4/80 (Adgre1), a marker of tissue-resident macrophages. NLRC5-deficient livers showed increased phosphorylation of the NF-κB subunit p65 that remained elevated following fibrosis induction. Taken together, NLRC5 deficiency deregulates hepatic inflammatory response following chemical injury but does not significantly aggravate the fibrogenic response, showing that NLRC5 is not a critical regulator of liver fibrosis pathogenesis.